Patient characteristics and outcome of IVUS-facilitated Management in Intermediate Coronary Lesion - Tripathi, Prashant Mani; Dahal, Manish; Khanal, Raja Ram; Devkota, Surya; Gajurel, Ratna Mani; Poudel, Chandra Mani (Nepalese Heart Journal, 2026)
Background and Aims: Intravascular ultrasound enables better quantitative assessment of the vessel wall. In this study we aim to investigate the patient characteristics, lesion characteristics and outcome of IVUS facilitated coronary angiography and angioplasty in patients with Intermediate coronary lesion. Method: Cross-sectional, Quantitative study done at MCVTC (IOM) for 1 year. Random, Nonprobability sampling was used. All the patients with Intermediate coronary artery disease who underwent IVUS were included in the study. Patient characteristics, lesion characteristics, PCI and outcome were studied. Result: 33 cases who underwent IVUS were included in the study. The mean age was 56 years with 78% being male. On CAG LAD was the most common artery involved with 42% of cases followed by, RCA (30%) and LCx Involvement (21%) while only 7% cases had Left Main artery involvement. 23 (70%) of patient were managed medically and 10 (30%) were managed by PCI. Out of those managed with PCI, 2 (20%) had PCI in LAD, 4 (40%) had PCI in LCX and 4 (40%) had PCI in RCA. The mean MLA of LAD undergoing PCI was 3.8mm2 and % stenosis was 72%. Similarly, MLA in LCx undergoing PCI was 3.7mm2 and % stenosis was 76%. In RCA who underwent PCI mean MLA was 3.5mm2 and % stenosis was 78%. Conclusion: Routine use of IVUS in intermediate coronary artery lesion has a significant impact on identifying anatomically significant lesion which requires revascularization.